Sensitivity of SARS/MERS CoV to Interferons and Other Drugs Based on Achievable Serum Concentrations in Humans - R. Strayer, David; Dickey, Robert; A. Carter, William (Infectious Disorders - Drug Targets, 2014)
A novel coronavirus (MERS-CoV) related to SARS-CoV recently emerged in the Middle East causing more than 400 deaths with a mortality rate of about 30%, much higher than SARS-CoV. Both viruses target epithelial cells in the respiratory tract, although utilizing different cellular receptors. Because of the sporadic nature of the MERS outbreak and difficulty in collecting randomized, controlled clinical data, the objective of this review was to focus on published in vitro and in vivo drug sensitivity data using both cell lines and available animal models of SARS/MERS CoV infection. Determination of drug activity was based on achievable serum levels in humans relative to in vitro IC50 (50% inhibitory concentration) or EC50 (50% effective concentration) drug concentrations. The most active drugs against SARS/MERS CoV at clinically achievable serum levels were type I interferons and a TLR3 agonist, interferon inducer/activator.
Keywords: interferons